Impact of health education regarding personal hygiene and dietary habits on morbidity profile of students: an intervention study in a government secondary school in a slum area of Kolkata - Pal, Jayita; Pal, Arghya K. (International Journal Of Community Medicine And Public Health, 2017)
Background: Most of the morbidities among school children are preventable by ensuring healthy practices regarding personal hygiene and diet. The current study aimed to assess effectiveness of a health education programme regarding personal hygiene and diet in improving the morbidity profile of the adolescent girls in an urban slum. Methods: A quasi experimental study was conducted in two Government secondary schools located in a slum area of Kolkata. The study consisted of three steps. First a baseline survey with the help of a predesigned pretested questionnaire and checklist was done to find out the socio-demographic information and existing knowledge, attitude, practice of personal hygiene and dietary habits of the students. Morbidity profile of the children was also assessed. This was followed by an intervention phase of 6 months during which weekly lecture and demonstration classes were taken in the study school. Second step was reassessment of morbidities by clinical examination at post intervention. Third step was to follow them for another 3 months to reassess their morbidities. Results: There was statistically significant decrease in the prevalence of morbidities in study school from the pre-test level to post-test level as compared to the control school, but the effect was not sustained at follow up as shown by increase in mean morbidity score at 9 months follow up than 6 months post-intervention level in the study school. Conclusions: Sustained behavioral change programme regarding proper practice of personal hygiene and diet could significantly decrease the prevalence of major morbidities encountered in adolescent girl students.